Measurement of small vessel machinery vibration induced acoustic signature levels - Pavan Kumar, GVV; Prasad, V V S; Nagesh, B H (Journal of Naval Architecture and Marine Engineering, 2019)
Ship vibrations, airborne and underwater noise levels have always been a challenging topic from a performance point of view in ship design, building and operation. The measurement shall help in monitoring the self-noise and the technical state of their machinery mechanism. The vibration levels on the main engine and auxiliary Genset foundation, airborne noise levels of the engine room and underwater self-noise levels of a small mechanized fishing trawler was measured at the jetty in idling condition. The vibration levels on the foundation measured the average value of 0.207 mm/s for the main engine and 1.36 mm/s for auxiliary Genset. The airborne noise levels measured 99 dB (A) in the engine room. The peak underwater sound pressure levels measured 162 dB re 1µPa. The response spectra indicate the peak vibration and noise levels in the lower frequency region <1.2 kHz. The machinery excitation forces transferred to the hull surface as pressure fluctuations which generated the airborne and underwater noise levels. Though the measurement limited to jetty conditions, detailed analysis can be useful for detection, classification, and tracking of small vessels.